Real-time radiation dosimetry using P-doped silica optical fiber. (November 2019) - Zubair, H.T.; Oresegun, A.; Rahman, A.K.M. Mizanur; Ung, N.M.; Mat Sharif, K.A.; Zulkifli, M.I.; Yassin, S.Z. Muhd; Maah, M.J.; Yusoff, Z.; Abdul-Rashid, H.A.; Bradley, D.A.; Omar, Nasr Y.M.
Highlights: P-doped silica optical fiber produces radioluminescence under MV X-ray exposure. Real-time, remote reading achieved through fiber-optic coupled configuration. Emission is consistent for a particular dose-rate producing flat top response. Absence of memory effect makes possible successive measurement without annealing. Integration of radioluminescence photon counts provides reliable estimate of dose. Abstract: Radiation dosimetry applications related to radiotherapy have clear importance in determining the accurate and safe delivery of patient prescribed doses. Versatile yet robust, high spatial resolutions, wide dynamic range real-time forms of dosimetry are called for. Doped silica optical fibers of sub-mm spatial resolution exhibit useful radioluminescence (RL) properties when exposed to ionizing radiation. In this study, primary investigations have been carried out on phosphorus-doped silica optical-fiber. High-energy clinical X-ray beams (6 MV and 10 MV) were used to irradiate the optical fiber, RL response being recorded for six dose-rates (between 100 MU/min and 600 MU/min) delivered by a Varian 2100 C/D linear accelerator. The P-doped optical-fiber showed linear RL response, with minimal observable memory and afterglow and plateau effects. The results indicate the P-doped optical-fiber dosimeter to have strong potential for use in radiotherapy applications.